2016
DOI: 10.1103/physrevb.94.205424
|View full text |Cite
|
Sign up to set email alerts
|

Quantum interference effects in topological nanowires in a longitudinal magnetic field

Abstract: We study the magnetoconductance of topological insulator nanowires in a longitudinal magnetic field, including Aharonov-Bohm, Altshuler-Aronov-Spivak, perfectly conducting channel, and universal conductance fluctuation effects. Our focus is on predicting experimental behavior in single wires in the quantum limit where temperature is reduced to zero. We show that changing the Fermi energy EF can tune a wire from from ballistic to diffusive conduction and to localization. In both ballistic and diffusive single w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…In addition, the temperature dependence of ABOs follows the diffusive 16,19 or quasi-ballistic 14,17,20 transport behavior for the same kind of NRs with similar geometric dimensions. Finally, the crossover between AB and AAS oscillations in TI NRs is expected based on theory 11,24 ; however, its experimental verification has not been performed yet.…”
mentioning
confidence: 98%
“…In addition, the temperature dependence of ABOs follows the diffusive 16,19 or quasi-ballistic 14,17,20 transport behavior for the same kind of NRs with similar geometric dimensions. Finally, the crossover between AB and AAS oscillations in TI NRs is expected based on theory 11,24 ; however, its experimental verification has not been performed yet.…”
mentioning
confidence: 98%
“…The interplay between the disorder and the perfectly transmitted mode was further investigated in ref. [16].…”
Section: Transport In Quantum Confined Topological Insulatorsmentioning
confidence: 99%
“…[ 1 ] Such new properties have direct consequences on the quantum transport of Dirac fermions, showing a very rich physics that can be revealed in simple geometries of mesoscopic conductors such as nanowires (NWs) or nanoribbons. [ 4–20 ]…”
Section: Introductionmentioning
confidence: 99%
“…We performed numerical simulations of conduction in single TI wires where the scattering length was comparable to or longer than the wire perimeter, but was much smaller than the wire length, putting each wire in the diffusive regime. 22 We showed that in a single wire [or nanotube, etc.] ALL winding numbers will be seen, including AB oscillations, AAS oscillations, and all higher winding numbers.…”
Section: Magnetic Phase Effects In Wiresmentioning
confidence: 99%